Integration of Islamic Religious Education and Local Wisdom in Forming Multicultural Character - Sodikin Sodikin; Ahmad Syahid; Arifuddin M. Arif; Adawiyah Pettalongi (Institut Agama Islam Daruttaqwa Gresik, 2026)
Indonesia, as a multicultural nation, faces the challenge of increasing intolerance and exclusive attitudes among adolescents, indicating a suboptimal internalization of multicultural values ​​in education. At the madrasah level, Islamic Religious Education (PAI) plays a strategic role in character formation, but its implementation is often normative-doctrinal and poorly connected to students' socio-cultural context. This study aims to analyze the form of collaboration between PAI and local culture in instilling multicultural values at MTs Al Barakah Rojo, examine the ongoing process of value internalization, and formulate an applicable, contextually relevant conceptual model. This study employed a descriptive qualitative approach, with data collection techniques including observation, in-depth interviews, and documentation. Informants included the madrasah principal, Islamic Religious Education teachers, other subject teachers, and students. Data analysis was conducted through the stages of reduction, presentation, and conclusion, using triangulation of sources and techniques to ensure the validity of the findings. The research results show that the collaboration between Islamic Religious Education (PAI) and local culture is realized through the integration of Islamic brotherhood values ​​with cooperation, the inculcation of madrasah culture (greetings, deliberation, community service), dialogic learning, socio-religious activities based on local traditions, and teacher role models. This process internalizes values cognitively, affectively, and psychomotorically, thereby forming tolerant, inclusive, empathetic, and moderate students. The implications of this research underscore the importance of an integrative model grounded in the madrasah ecosystem as an effective strategy for strengthening multicultural education and religious moderation.